Perturbations of the arginine metabolome following exposures to traffic-related air pollution in a panel of commuters with and without asthma. (June 2019) - Liang, Donghai; Ladva, Chandresh N.; Golan, Rachel; Yu, Tianwei; Walker, Douglas I.; Sarnat, Stefanie E.; Greenwald, Roby; Uppal, Karan; Tran, ViLinh; Jones, Dean P.; Russell, Armistead G.; Sarnat, Jeremy A.
Abstract: Background: Mechanisms underlying the effects of traffic-related air pollution on people with asthma remain largely unknown, despite the abundance of observational and controlled studies reporting associations between traffic sources and asthma exacerbation and hospitalizations. Objectives: To identify molecular pathways perturbed following traffic pollution exposures, we analyzed data as part of the Atlanta Commuters Exposure (ACE-2) study, a crossover panel of commuters with and without asthma. Methods: We measured 27 air pollutants and conducted high-resolution metabolomics profiling on blood samples from 45 commuters before and after each exposure session. We evaluated metabolite and metabolic pathway perturbations using an untargeted metabolome-wide association study framework with pathway analyses and chemical annotation. Results: Most of the measured pollutants were elevated in highway commutes ( p < 0.05). From both negative and positive ionization modes, 17, 586 and 9087 metabolic features were extracted from plasma, respectively. 494 and 220 unique features were associated with at least 3 of the 27 exposures, respectively ( p < 0.05), after controlling confounders and false discovery rates. Pathway analysis indicated alteration of several inflammatory and oxidative stress related metabolic pathways, including leukotriene, vitamin E, cytochrome P450, and tryptophan metabolism. We identified and annotated 45 unique metabolites enriched in these pathways, including arginine, histidine, and methionine. Most of these metabolites were not only associated with multiple pollutants, but also differentially expressed between participants with and without asthma. The analysis indicated that these metabolites collectively participated in an interrelated molecular network centering on arginine metabolism, underlying the impact of traffic-related pollutants on individuals with asthma. Conclusions: We detected numerous significant metabolic perturbations associated with in-vehicle exposures during commuting and validated metabolites that were closely linked to several inflammatory and redox pathways, elucidating the potential molecular mechanisms of traffic-related air pollution toxicity. These results support future studies of metabolic markers of traffic exposures and the corresponding molecular mechanisms. Highlights: Traffic exposure strongly associated with oxidative stress and inflammation pathways. 45 unique metabolites associated with traffic identified, including arginine and histidine. Asthma status modify associations between metabolic perturbations and traffic exposure. Differential perturbations in arginine metabolome observed in commuters with and without asthma. Potential mechanism of traffic-related pollutants toxicity in individuals with asthma revealed.